Heat Transfer Analysis for Couple Stress Fluid over a Nonlinearly Stretching Sheet - Khan Najeeb Alam; Riaz Fatima; Khan Nadeem Alam (Nonlinear Engineering, 2013)
An investigation has presented to analyze the heat transfer in a boundary layer flow of an incompressible couple stress fluid over a nonlinear stretching sheet. The heat transfer problem have been analyzed for the two heating processes, 1) PST (prescribed surface temperature case) and 2) PHF (prescribed heat flux case). The governing partial differential equations for flow and heat transfer are transformed to ordinary differential equations. The numerical solutions have been obtained by using fourth order Runge-Kutta method coupled with shooting method. The effects of dimensionless surface temperature, couple stress parameter beta, Prandtl number Pr, Eckert number Ec, nonlinear stretching sheet parameter n and lambda1; lambda2 have been observed by graphical illsurations.